Планування мереж абонентського доступу xDSL - Бриндзій, О. В.; Агеєв, Д. В. (Проблеми телекомунікацій, 2011)
We propose xDSL subscriber access networks planning method, which allows determine the optimal scenario of building FTTx network and DSLAM equipment installation places. The proposed method is implemented on a PC and a study of its effectiveness.
Keywords: xDSL; планування абонентського доступу